A comparative study of mud‐like and coralliform calcium carbonate gallbladder stones. Issue 7 (28th February 2017) - Ma, Rui‐Hong; Luo, Xiao‐Bing; Wang, Xiao‐Feng; Qiao, Tie; Huang, Hai‐Yi; Zhong, Hai‐Qiang
Abstract: To gain insight to underlying mechanism of the formation of calcium carbonate (CaCO3 ) gallbladder stones, we did comparative study of stones with mud appearance and those with coralliform appearance. A total of 93 gallbladder stones with mud appearance and 50 stones with coralliform appearance were analyzed. The appearance, color, texture, and the detection of Clonorchis sinensis eggs by microscopic examination were compared between the two groups. Then, the material compositions of stones were analyzed using Fourier Transform Infrared spectroscopy and the spectrogram characteristics were compared. Moreover, microstructure characteristics of the two kinds of stones were observed and compared with Scanning Electron Microscopy. Mud‐like gallbladder stones were mainly earthy yellow or brown with brittle or soft texture, while coralliform stones were mainly black with extremely hard texture, the differences between the two groups was significant ( p < .05). The analytic results of FTIR spectroscopy showed that 95.7% (89/93) of the mud‐like gallbladder stones were CaCO3 stones, and mainly aragonite; while all of the coralliform stones were CaCO3 stones, and mainly calcite ( p < .05). Meanwhile, microscopic examination indicated that the detection rate of Clonorchis sinensis eggs in mud‐like CaCO3 stones was lower than that in coralliform CaCO3 stones ( p < .05), and that in aragonite CaCO3 stones was lower than that in calcite CaCO3 stones( p < .05). Mud‐like CaCO3 stones mainly happened to patients with cystic duct obstruction. Clonorchis sinensis infection was mainly associated with coralliform (calcite) CaCO3 stones. Cystic duct obstruction was mainly associated with mud‐like (aragonite) CaCO3 stones. Abstract : Previous study showed that calcium carbonate stones were mainly mud‐like or coralliform. The present study found that the appearance, color, texture, crystalline forms and the detection of C. sinensis eggs were different between the two kinds of stones. C. sinensis infection was mainly associated with coralliform (calcite) calcium carbonate stones. Cystic duct obstruction was mainly associated with mud‐like (aragonite) calcium carbonate stones.